Influence of strands transposition on current distribution and power losses in windings of AC machines - Tomičić, Branko, inženjer elektrotehnike (Array, 2018)
This paper analyses how the type of winding affects the current distribution and power losses in armature winding. Using finite element method, four different types of winding used in large asynchronous motors are analyzed: form-wound concentric, with and without transposition, and form-wound barrel, with and without transposition, for the stationary state. In two cases, the calculation shows clear differences between maximum currents in strands, a shift in their phases, and a resulting increase of AC resistance. In two other cases, minor deviations, smaller phase shift and smaller increase of AC resistance, are detected. It indicates that in certain types of armature winding of large motors the strands transposition leads to significant positive effects in terms of motor power, while in other cases it leads to unnecessary complications making the manufacture of large asynchronous machines more difficult, with relatively small positive effect on the motor power losses.